(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2019)
Soil salinity is a worrying factor for agriculture in the arid and semiarid regions due to the soil and climatic conditions and the irrigated agriculture that has been practiced. Brachiaria decumbensis a forage species exploited in these regions where its cultivation is usually linked to irrigated systems. The aim of this work was to evaluate the effect of sanility on growth of Brachiaria decumbensat different levels of salinity. The experiment was carried out in greenhouse in Feira de Santana, Bahia State, Brazil. Brachiaria seedlings were submitted to five levels of salinity (0, 2, 4, 8 e 16 dS.m-1) and three replicates. All analyzed variables presented negative linear response to saline doses. The reductions in the variables were more accentuated in 16 dS.m-1, classifying this species as sensitive to the salinity of irrigation water.